Talking about the Vaccine after the Pandemic: A Cross-Sectional Study among Youth in Turkey and Ethical Issues - Özdinç, Ahmet; Değer, Mehmet Sait; Atak, Muhammed; Demir, İbrahim (Vaccines (Basel), 2023)
Examining the factors that affect the vaccination rate among young people in an ethical frame can support vaccination promotion. Therefore, this study will elaborate, through an ethical lens, on young people’s hesitation about and decisions regarding getting vaccinated. The cross-sectional study was conducted with 2428 people aged 15–30 in Turkey in June 2022. The questionnaire included the following subtitles: psycho-social situation, health services and health policies, COVID-19 vaccine, and predictions about life and health after the pandemic. The average age was 22.9 years. In the study sample, 80% were vaccinated, while 20% were not. Vaccinated participants acted more cautiously to protect their health. Receiving accurate and sufficient information on proposed vaccines affects vaccination status. The primary reason for getting vaccinated was “to protect their health, families, and relatives”, and the primary reason for not getting vaccinated was “not trusting the vaccine content or the country where the vaccine was produced”. Specifically, those vaccinated felt more relaxed physically, psychologically, and socially. In addition, the expectations for the future of those vaccinated were significantly higher. Accurate and adequate information is essential for reducing vaccine hesitancy. In addition, promoting prosocial behaviors in young people and highlighting related values will support vaccination.